HUBUNGAN KEKERABATAN BAHASA PALEMBANG DAN BAHASA BANGKA MELALUI ANALISIS KOGNAT - Zuansyah, Najmah (Metahumaniora, 2026)
This study aims to identify the relationship between Bangka (BB) and Palembang (BP) languages through cognate analysis using lexicostatistics and glottochronology methods. The research data consists of 200 basic Swadesh vocabulary items analysed based on similarity of form, vowel and consonant correspondence, and phonological changes. The results of the study showed that 64 cognate words were found, with a percentage of relatedness of 32%, which confirms that the two languages belong to the same family, although they are not closely related. Analisis korespondensi bunyi memperlihatkan pola perubahan fonologis yang sistematis, di mana BB cenderung mengalami lebih banyak inovasi fonologis ketimbang BP yang bersifat lebih konservatif. Through glottochronological calculations, it is estimated that BB and BP diverged around 2,714 years ago, with a margin of error of ±225 years. These findings suggest that linguistic divergence occurred gradually and was influenced by geographical, social and cultural factors.